Bahasa Indonesia PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PADA MATERI INTERAKSI ANTAR MAKHLUK HIDUP KELAS VII SMP - Maulidina Khairunnisa'; Sutarno Sutarno; Harlita Harlita (Postgraduate, University of Mataram, 2024)
The type of research used is R&D (Research and Development). Research and Development. The development model used is the ADDIE model (Analysis, Design, Development, Implementation and Evaluations). The research sample involved 132 students consisting of 66 students each at MTSN Filiah and MTS N Sukoharjo. The characteristics of E-Modules are simple, interactive, and communicative. In addition, Emodul has been integrated with the discovery learning model that can encourage students' science process skills. The discovery-based E-Module developed is considered feasible to be used as learning media to improve students' science process skills. This can be seen from the average value of the percentage of eligibility acquisition on Discovery learning-based E-Modules ranging from 0.71% with a moderate category. Discovery-based E-Modules have a high level of effectiveness where the results of the analysis show that the significance value of Sig.2-tailed (0.00) <0.05, indicating a significant difference between pretests and postsets. This shows that there is a significant difference in effect with E-modules based on discovery learning between pretest and posttest